2016
DOI: 10.1186/s40504-016-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of emerging science and technologies as creating learning processes among assessment communities

Abstract: Emerging science and technologies are often characterised by complexity, uncertainty and controversy. Regulation and governance of such scientific and technological developments needs to build on knowledge and evidence that reflect this complicated situation. This insight is sometimes formulated as a call for integrated assessment of emerging science and technologies, and such a call is analysed in this article. The article addresses two overall questions. The first is: to what extent are emerging science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…On the other hand, focusing on the analysis of undesirable effects in day-to-day work of R&I practitioners may lead to RRI becoming an integral part of the design process. This can be done following the example of risk analysis for product safety, which is an integral part of R&D. This compromise, however, is in line to the statements made by Forsberg et al (2016), which stated that there is a difference between the bird's eye view and to really zoom in on the details to make the results applicable to daily practice. This difference must also be reflected in the methodological support and somehow be brought together.…”
Section: Notes For the Successful Application And Adaption Of Amicaimentioning
confidence: 88%
See 3 more Smart Citations
“…On the other hand, focusing on the analysis of undesirable effects in day-to-day work of R&I practitioners may lead to RRI becoming an integral part of the design process. This can be done following the example of risk analysis for product safety, which is an integral part of R&D. This compromise, however, is in line to the statements made by Forsberg et al (2016), which stated that there is a difference between the bird's eye view and to really zoom in on the details to make the results applicable to daily practice. This difference must also be reflected in the methodological support and somehow be brought together.…”
Section: Notes For the Successful Application And Adaption Of Amicaimentioning
confidence: 88%
“…However, the undesirable effects of research and innovation cannot be ignored and must therefore be part of RRI. The importance of problem-orientation in emerging science and technologies assessment is, for example, discussed by Forsberg et al (2016). Chatfield et al (2017) concluded that employing the theoretical lens of risk in a pragmatic "first step" approach can be a familiar language to companies and thus R&I practitioners.…”
Section: Notes For the Successful Application And Adaption Of Amicaimentioning
confidence: 99%
See 2 more Smart Citations
“…Generally RRI emphasizes consideration of ethical and social aspects of research and innovation in addition to natural sciences, and therefore asks to combine assessments from different perspectives. To this end, the TranSTEP approach was developed, which pleads for maximizing the integration of various existing assessment methodologies including, for example, technology assessment (TA), risk analysis (RA), and life cycle analysis (LCA) (Forsberg et al ).…”
Section: Some Background On Responsible Research and Innovationmentioning
confidence: 99%